PERKAWINAN DALAM ADAT MENURUT HUKUM NASIONAL (STUDI PERKAWINAN PARIBAN PADA MASYARAKAT ADAT BATAK TOBA DIKECAMATAN SIAK HULU KABUPATEN KAMPAR PROVINSI RIAU) - Ria Okta Meliana S; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Pariban marriage for Batak people is married sons with mother's daughter of mother's brother (toba: borunitulang) and married daughter with male child of father's sister. Marriage is prohibited in certain relationships and circumstances according to religion and / or law, for example because the blood relationship is too close, because semenda, has divorced three times, or has not yet expired waiting period. If a marriage takes place when there is a prohibition or not fulfilled the conditions, the marriage is canceled. Some of them already know that pariban is an ancient marriage legacy of a unique batak people and sometimes seems irrational again for now. Pariban is usually recommended for family or for marriage. The purpose of this thesis writing are: First, to know the implementation of marriage pariban on indigenous people batak toba dikecamatan Siak upstream Kampar district riau province. Second, to know the validity of pariban marriage when associated with Law Number 1 Year 1974 About Marriage.The type of this research is Juridical Sociological research, because in this research the author directly conduct research on the location under study in order to give a complete and clear description of the problem under study. This research was conducted on indigenous people Batak Toba Siak Hulu Kampar regency, while population and sample are all parties related to the problem studied in this research, data source used primary data, secondary data and tertiary data, data collection technique in this research with interviews and literature studies.From the research results of the problem there are two main points that are concluded, First, the implementation of pariban marriage in indigenous people Batak toba Siak upstream Kampar district Riau province is an ideal marriage conducted for generations. Second, the validity of the marriage when associated with Law No. 1 of 1974 on Marriage that regulates everything about marriage both materially and formally in Indonesia.Keywords: Marriage – Pariban – Implementation